Perlindungan Hak Tenaga Kerja Terhadap Buruh Perempuan Yang Mendapatkan Ketidakadilan di Tempat Kerja (Studi Kasus PT. AFI) - Hidayat, Muhammad Rahmadzani; Aini, Qurrotul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article discusses the injustices experienced by female workers at PT. AFI, where women are often placed in jobs that are not equal to their abilities and are threatened with dismissal if they do not comply. This reflects gender-based discrimination in the world of work. Injustice towards female workers still often occurs even though there are various regulations that protect their rights, such as Law Number 13 of 2003 concerning Employment and other regulations that guarantee the right to leave for menstruation, pregnancy, childbirth and breastfeeding. The implementation of this law is often ineffective, so that many complaints from female workers are ignored. The legal prevalence of female workers must be more enforced and companies must be committed to fulfilling their rights to create a fair and supportive work environment. In this research, the author applies normative juridical research methods through the use of several approaches, namely the Statutory Approach, the Conceptual Approach, and the Case Approach. It is hoped that the resulting research will provide broad benefits to the general public by broadening their understanding regarding the prevalence of women in the workforce or injustice in the work environment based on applicable laws.